A bio-inspired swarm intelligence technique for social aware cognitive radio handovers. (October 2018) - Anandakumar, H.; Umamaheswari, K.
Abstract: A novel dynamic spectrum sharing method inspired by natural communities based on social language has been proposed to overcome prevailing spectrum underutilization and scarcity. The Social Cognitive Radio Network (SCRN) combines social data and mobile communication network by providing a range of data delivery services concerning social relationship among mobile users. The research focuses on diverse SCRN applications and its handover issues, a bio-intelligent supervised learning approach called SpecPSO is devised for performing social cognitive handover (SCH) to: a) Evaluate efficient spectrum utilization and b) Increase data rate for applications like Facebook, LinkedIn. Experimental results show that the proposed SCH-SpecPSO outperforms 75% more than state of art mobile social networks by optimizing various handover issues.